The Messages of Islamic Communication at One Roof System (SAMSAT) Sibolga, Indonesia - Hakim Hakim; Syukur Kholil; Yusnadi Yusnadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This research deals with the messages of Islamic communication at one roof system (Samsat) Sibolga, Indonesia. This research is conducted by using qualitative approach. The result shows that Samsat city uses communication patterns and other forms of communication which are divided into four forms, there are: Intra-personal communication (communicating with oneself), Inter-personal communication (communicating privately between one person and one person), group communication and organizational communication. These communication is carried out by all parties related to the records must be carried out outside of working hours. Services provided at one roof system (Samsat) Sibolga city are carried out by all Samsat officer starting from parking staff to service officer with the aim of effective Samsat services in Sibolga city. Communication messages which are conveyed by Samsat Sibolga City are divided into three things, there are: true and firm words and good (Qaulan Sadida), Fragile words, (Qaulan Balighah), and easy-to-understand words (Qaulan Layina). In addition, communication messages to be conveyed by Samsat Sibolga City also have other aims, there are: 1. Comply with the state administration including administration of compliant vehicles 2. Inviting actively and on target, as well as good management institutionally